Body-led mothering: Constructions of the breast in attachment parenting literature. (May 2017) - Carter, Shannon K.
Abstract: The breast is absent in much breastfeeding literature, yet it is central to political controversies surrounding breastfeeding in public. This study examines social constructions of the breast in Attachment Parenting literature on breastfeeding. Attachment Parenting, an approach growing in popularity in many western societies, advocates breastfeeding as a core component of parenting and is consistent with broader mothering ideals. Findings indicate that the breast is constructed as the ultimate mother – engaging in practices that mirror idealized depictions of hegemonic motherhood toward both the baby and the mother. The texts represent the breast engaging in body-led mothering by providing nurturing and protection to both baby and mother, and teaching the mother how to mother her baby. These depictions corroborate essentialist views of femininity and mothering in western societies by locating socially defined characteristics within the female body, and contribute to views of the breastfeeding breast as inherently motherly rather than sexual.